Green synthesis of Ag/TiO2 Nanocomposite Assisted by Gambier Leaf (Uncaria gambir Roxb) Extract - Sry Wahyuni; Syukri Syukri; Syukri Arief (Jurnal Kimia Sains dan Aplikasi, 2019)
Studies of green synthesis of nanoparticles mediated by plants extract is extensively explored and studied in recent time due to eco-friendliness, cost-effectiveness, and use a minimum amount of toxic chemicals in the process of inorganic material synthesis. In this study, the immobilization of silver nanoparticles on the surface of titanium dioxide (TiO2) was carried out using Uncaria gambier Roxb. leaf extract as a silver ion (Ag+) reducing agent. The synthesized Ag/TiO2 nanocomposite was characterized by UV-Vis spectroscopy, X-ray diffraction (XRD), and Diffuse Reflectance Spectroscopy (DRS). The formation of silver nanoparticles was confirmed through UV-Vis spectroscopic analysis, which showed a silver surface plasmon resonance (SPR) band at 426 nm. The X-ray diffraction pattern shows that Ag can inhibit the transition of the anatase into rutile phase. The presence of Ag particles in TiO2 can increase the absorption ability from an initial wavelength of 407 nm to 438 nm. Based on the results of Rhodamin B degradation, it can be seen that Ag/TiO2 has a higher photocatalytic activity than bare TiO2 with 99% percent degradation at 120 minutes of irradiation time.